Comparative Interpretation of CT and Standard Radiography of the Pleura - Bart Ilsen; Frederik Vandenbroucke; Cathérine Beigelman-Aubry; Carola Brussaard; Johan de Mey (Journal of the Belgian Society of Radiology, 2016)
Many diseases affect the pleural space in both adults and children, including common diseases such as pneumonia, cancer and heart failure. Pleural effusion is the most common manifestation of pleural disease, and it is often a secondary effect of another disease process. Imaging plays a crucial role in the management of pleural disease. Chest radiography often remains the first examination in the assessment of these patients. Depending on the clinical context, the optimal imaging technique for further evaluation might be computed tomography (CT), ultrasound (US), or magnetic resonance (MR).